Liability to Master for Negligent Harm to Servant - Warren A. Seavey (Washington University Law Quarterly, 1956)
It is quite clear today that the relation of master and servant, no longer represents the close bond which it once did. It is equally clear that a servant no longer regards himself as his master's man, but as an independent person who can bargain effectually. There is no longer anything which even remotely resembles what was formerly thought of as the status of a servant. Although there is still a fiduciary relation, the bond is primarily contractual with rights and duties in many cases spelled out in great detail. Bearing in mind, therefore, the great difference between the modern industrial servant and the servant in the early centuries of the English common law, the question arises whether the liability placed upon a person who negligently harms a servant should continue in view of the change in the relation.
Keywords: Negligence; Employer and employee; Master & amp; Servant